2019
DOI: 10.1002/cpt.1716
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Mosquito‐Lethal Effects of Ivermectin in Combination With Dihydroartemisinin‐Piperaquine and Primaquine in Healthy Adult Thai Subjects

Abstract: Mass administration of antimalarial drugs and ivermectin are being considered as potential accelerators of malaria elimination. The safety, tolerability, pharmacokinetics, and mosquito-lethal effects of combinations of ivermectin, dihydroartemisinin-piperaquine, and primaquine were evaluated. Coadministration of ivermectin and dihydroartemisinin-piperaquine resulted in increased ivermectin concentrations with corresponding increases in mosquito-lethal effect across all subjects. Exposure to piperaquine was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 43 publications
1
75
1
Order By: Relevance
“…The insecticidal activity of ivermectin and its specific effect on Anopheles mosquito prompted an investigation into its antiplasmodial activity against the malaria parasite in order to use it for malaria treatment [102]. The antiplasmodial and insecticidal effects of ivermectin often depend on the concentration, route of administration, duration, species type, and experimental design [103]. Ivermectin was reported to inhibit the development of P. falciparum at the asexual stage with IC 50 in the range of 1-10 µg/mL, however, ivermectin had no effect at concentrations of 3.9-1000 ng/mL on P. vivax [104].…”
Section: Endectocides For Malaria Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The insecticidal activity of ivermectin and its specific effect on Anopheles mosquito prompted an investigation into its antiplasmodial activity against the malaria parasite in order to use it for malaria treatment [102]. The antiplasmodial and insecticidal effects of ivermectin often depend on the concentration, route of administration, duration, species type, and experimental design [103]. Ivermectin was reported to inhibit the development of P. falciparum at the asexual stage with IC 50 in the range of 1-10 µg/mL, however, ivermectin had no effect at concentrations of 3.9-1000 ng/mL on P. vivax [104].…”
Section: Endectocides For Malaria Controlmentioning
confidence: 99%
“…A different observation on the process by which ivermectin inhibits the growth of mosquitoes when infected with P. falciparum [106]. Kobylinski et al [103] reported that ivermectin decreased the intensity and prevalence of oocyst in different mosquitoes, while de Carvalho et al and Perez-Garcia et al [104,107] reported a reduction in the prevalence of oocyst without affecting the intensity in mosquito infected with P. falciparum and P. vivax. Three different avermectins were also tested with respect to the hepatic effect of Plasmodium.…”
Section: Endectocides For Malaria Controlmentioning
confidence: 99%
“…Venous blood was collected from three healthy Thai volunteers given a single dose of IVM (400 μg/kg) (NCT02568098) (Kobylinski et al, 2020). The blood samples were collected in sodium heparin tubes at 24 hours post IVM ingestion and kept frozen at -80°C until LC-MS/MS analysis.…”
Section: Healthy Volunteer Samplesmentioning
confidence: 99%
“…Malaria is a mosquito-borne disease transmitted by Anophelesmosquitoes during blood feeding. Numerous studies have reported the mosquito-lethal effect of ivermectin (Chaccour et al, 2013;Kobylinski et al, 2020;Smit et al, 2018) and the ability to inhibit sporogony ofPlasmodium in the mosquito (Kobylinski et al, 2012;Kobylinski et al, 2017;Pinilla et al, 2018). Mass drug administration (MDA) of IVM has been suggested as a possible vector control tool to aid malaria elimination as it has been shown to reduce Plasmodiumtransmission by mosquitoes (Alout et al, 2014) and reduce transmission to humans (Foy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation